2019
DOI: 10.1371/journal.pone.0214622
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activity is upregulated in an in-vitro model of COPD exacerbation

Abstract: Background Chronic obstructive pulmonary disease (COPD) is an inflammatory disease characterized by a progressive and irreversible deterioration of lung function. Exacerbations of COPD have prolonged negative effects on pulmonary function and a major impact on health status and outcomes. NLRP3 inflammasome is a cardinal component of the inflammatory response, with marked evidence in stable and exacerbations of COPD. The aim of our study was to evaluate the NLRP3 inflammasome activity during COPD e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…The NLRP3 inflammasome has attracted much attention as a therapeutic target, due to its disease‐inducing roles in many inflammatory diseases, including arthropathy, COPD, inflammatory bowel disease, multiple sclerosis, Parkinson's disease, diabetes, and severe asthma 5,6,8–10,66,67 . For instance, the essential role of NLRP3 inflammasome is well presented in multiple chronic inflammatory lung diseases, such as asthma and COPD.…”
Section: Inflammasomes: Key Mediators Of Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLRP3 inflammasome has attracted much attention as a therapeutic target, due to its disease‐inducing roles in many inflammatory diseases, including arthropathy, COPD, inflammatory bowel disease, multiple sclerosis, Parkinson's disease, diabetes, and severe asthma 5,6,8–10,66,67 . For instance, the essential role of NLRP3 inflammasome is well presented in multiple chronic inflammatory lung diseases, such as asthma and COPD.…”
Section: Inflammasomes: Key Mediators Of Inflammatory Diseasesmentioning
confidence: 99%
“…Inflammasomes are innate immune system mediators that induce and regulate inflammation upon challenge by pathogens and environmental allergens. They are linked to a myriad of autoimmune and inflammatory diseases, including multiple sclerosis, Alzheimer's disease, atherosclerosis, diabetes, inflammatory bowel disease, severe asthma and chronic obstructive pulmonary disease (COPD) 3–10 …”
Section: Introductionmentioning
confidence: 99%
“…A549 cells maintain the type 2 AEC characteristics such as multilamellar bodies containing phospholipids similar to primary type 2 AEC and have similar surfactant protein expression (Nardone and Andrews, 1979; Cooper et al, 2016). However, while A549 cells have served as a useful type 2 AEC model across varied pulmonary disease studies (e.g., Gonzalez-Juarbe et al, 2017; Laventie et al, 2019; Nachmias et al, 2019; Nickol et al, 2019), and are capable of self-renewal, this cell line is not capable of differentiating to type 1 AEC, and therefore, stimuli that would trigger type 1 differentiation in vivo would go unnoticed (Fuchs et al, 2003). We have earlier demonstrated that lung fibroblasts (WI-26 cells) are exquisitely susceptible to M. tb -induced lysis; whether they also support M. tb replication is not known (Kinhikar et al, 2010).…”
Section: Breaching the Alveolar Barrier To Disseminate Systemicallymentioning
confidence: 99%
“… 31 Anti-inflammatory diets emphasize the inclusion of herbs and spices which have known antioxidant and anti-inflammatory effects and may slow the progression of COPD in which NLRP3 inflammasome activation plays a critical pathogenic role. 32 , 33 With any prolonged illness, COVID-19 included, mental health can be compromised. In a period as short as 10 days, a Mediterranean style diet may result in improved mood and cognition.…”
Section: Dietmentioning
confidence: 99%